Controlled Bilateral Filter And Clahe Based Approach For Image Enhancement (International Journal of Engineering and Computer Science, 2014)
Image enhancement is a region of improving the visual clarity of the image in digital image processing. In this paper, we propose a new algorithm using CLAHE and unsharp masking with bilateral filter.  Enhancement  of contrast  and  sharpness  of  an  image  is  required  in  many applications. In applications like medical radiography enhancing movie  features  and  observing  the  planets  it  is  necessary  to enhance  the  contrast  and  sharpness  of  an  image.  Unsharp masking  is  good  tool  for  sharpness  enhancement;  it  is  an  anti-blurring  filter.  By  using  unsharp  masking  algorithm  for sharpness  enhancement,  the  resultant  image  suffering  with  two problems,  first  one  is  a  hallo  is  appear  around  the  edges  of  an image,  and  second  one  is  rescaling  process  is  needed  for  the resultant image. The aim of this paper is to enhance the contrast and sharpness of an image simultaneously and to solve the problems.  In the proposed algorithm, we can adjust the two parameters controlling the contrast and sharpness to produce the desired output.